(untitled) (Malaysian Journal of Learning and Instruction, 2019)
Purpose - Learner autonomy enables an individual to learn how to cope with novelties without getting any help from others. Considering the rapid changes and transformations of the 21st century, it has become essential for teachers to possess this characteristic. Moreover, measuring learner autonomy is required to determine their levels. Thus, the purpose of this two-phased study was to adapt the Autonomous Learning Scale into Turkish and to investigate academic motivation and self-efficacy as the predictors of autonomous learning. Methodology - In the first phase, the Autonomous Learning Scale was adapted into Turkish with the participation of 335 pre-service teachers. In the second phase of the study, the autonomous learning of pre-service teachers was investigated in terms of a number of demographic variables along with academic self-efficacy and academic motivation using the data obtained from 776 pre-service teachers with a survey method. Findings - For the first phase, the confirmatory factor analysis showed that Autonomous Learning Scale was a valid and reliable tool to be used in Turkish samples. For the second phase, the regression analysis revealed that academic self-efficacy and academic motivation were significant predictors of autonomous learning of pre-service teachers. Additionally, their autonomous learning significantly differed in terms of department, high school type, and gender. Furthermore, the GPAs of the pre-service teachers were significantly correlated with their autonomous learning levels. Significance - The Turkish version of the Autonomous Learning Scale was presented to researchers. The relationships between autonomous learning and self-efficacy along with motivation have been asserted in a number of studies. However, the present study not only confirmed the correlations among these variables, but also revealed the predictive powers of these variables on autonomous learning. Therefore, teacher educators and policy makers can gain insights from these findings.